Laser Cladding of Bronze on Aluminum Alloy - Abdulkarim A. Elalem (African Journal of Advanced Pure and Applied Sciences, 2025)
Laser cladding is considered as a strategic technique, since it can yield surface layers that, compared to other hard facing techniques, have superior properties in terms of, pureness, homogeneity, hardness, bonding and microstructure. A clad layer of bronze (6:6:3) formed on the Zl-105 aluminum alloy surface -using a high power CW CO2 laser. Effects of laser scanning rates on the quality of produced clad layer studied. The microstructure of clad layer examined using optical and scanning electron microscope. The produced phases and the chemical composition of the clad layer analyzed using XRD, and EDS. microhardness test profile indicated a significant improvement in the hardness of the bronze coating on the Zl-105Al.